PENINGKATAN HASIL BELAJAR KALKULUS MELALUI PEMBELAJARAN BERBASIS ANEKA SUMBER - Mirza, Ade; Pasaribu, Revi Lestari (Universitas Tanjungpura, 2024)
This research intends to build college student potency to understand and develop school mathematics by increasing college student studying results on calculus materials that are pointed out by their ability in recognition, representation, and translation. The problem that is assessed in this research is how to increase calculus studying results. What yielding learned college students on calculus materials could increase through learning gets sources on various basis? This research constitutes action research to 30 college students on faculty of teacher training and education at mathematics education study program, one that programmed integral calculus. Action intervention in this research is applied to learn to get sources from various basis, which is performed deep three cycles. Each cycle consists of thrice meetings. This observational result points out to mark sense result step-up studies college student, at least 85% entire college student gets achievement point 75.